Glutamate: The New Frontier in Pharmacotherapy for Cocaine Addiction - Uys, Joachim D.; LaLumiere, Ryan T. (CNS & Neurological Disorders - Drug Targets, 2008)
Considerable research into the neurobiology of cocaine addiction has shed light on the role of glutamate. Findings from models of relapse to cocaine-seeking indicate that the glutamatergic system is critically involved, as glutamate levels in the nucleus accumbens increase during reinstatement and glutamate receptor activation is necessary for reinstatement to drug-seeking. Thus, it would seem beneficial to block the increased glutamate release, but full antagonists of ionotropic glutamate receptors produce undesirable side effects. Therefore, modulation of glutamatergic transmission would be advantageous and provide novel pharmacotherapeutic avenues. Pharmacotherapies have been developed that have the potential to modulate excessive glutamatergic transmission through ionotropic and metabotropic (mGluR) glutamate receptors. Compounds that modulate glutamatergic transmission through ionotropic glutamate receptors include the non-competitive N-methyl-D-aspartic acid antagonists, amantadine and memantine, and the partial N-methyl-D-aspartic acid agonist d-cycloserine. They have shown promise in preclinical models of cocaine addiction. The mGluR2/3 agonist LY379268 is effective in inhibiting cocaine seeking in preclinical animal models and could decrease stress-induced relapse due to its anxiolytic effects. Similarly, the mGluR1/5 antagonists, 2-methyl-6-(phenylethynyl)pyridine and 3-[2- methyl-4-thiazolyl)ethynyl]pyridine, have shown to be effective in preclinical models of cocaine addiction. The cysteine pro-drug, N-acetylcysteine, restores the inhibitory tone on presynaptic glutamate receptors and has been effective in reducing cue-induced craving and cocaine use in humans. Furthermore, anticonvulsants, such as topiramate or lamotrigine, have shown efficacy in treating cocaine dependence or reducing relapse in humans. Future pharmacotherapy may focus on manipulating signal transduction proteins and pathways, which include Homer/N-methyl-D-aspartic acid complexes, to provide effective treatment for cocaine addiction.
Keywords: nucleus accumbens